Association between milk consumption and kidney stones in U.S. adults: results from NHANES 2007–2018 - Xie, Zhouzhou; Zhuang, Yiming; Peng, Shansen; Zhou, Xiaoqi; Zhang, Guihao; Jiang, Huiming; Zhang, Changyi; Chen, Nanhui (Frontiers in Nutrition, 2024)
Background: Dietary strategies play a crucial role in the prevention of kidney stones. While milk is known for its rich nutritional content, its impact on kidney stone formation remains unclear. This study aimed to examine the relationship between milk consumption and the risk of kidney stones among U.S. adults.Methods: We included 24,620 participants aged 20 and older from the National Health and Nutrition Ex-amination Survey (2007Survey ( -2018)). Milk consumption was defined based on each participant's response to the questionnaire item on "Past 30 day milk product consumption". Kidney stones history was self-reported by participants. The analysis employed weighted multivariate logistic regression models, followed by subgroup analyses for result validation, and explored the age-related dynamics of milk consumption's effect on kidney stone risk using a restricted cubic spline model.Results: Adjusted findings revealed that higher milk intake was associated with a decreased risk of kidney stones (odds ratio [OR] = 0.90, 95% confidence interval [CI] 0.85-0.96), notably among women (OR = 0.86, 95% CI 0.80-0.92) but not significantly in men (OR = 0.94, 95% CI 0.86-1.02). Smoothed curves across all ages showed that women consuming milk had a lower incidence of kidney stones than those who did not, particularly with regular consumption.Conclusion: This study uncovered that across all age groups, higher frequency of milk consumption in women is associated with a reduced risk of kidney stones. However, further prospective cohort studies are needed to confirm this finding.